Analisis Hukum terhadap Klaim Greenwashing Akuntabilitas Hukum di Era Branding Berkelanjutan - Raharjo, Budi; Kossay, Methodius (Hakim: Jurnal Ilmu Hukum dan Sosial, 2025)
Greenwashing poses significant challenges to sustainability initiatives in Indonesia, where weak regulatory frameworks and inconsistent enforcement exacerbate the issue. This study explores the interplay between greenwashing practices and legal regulations, aiming to identify gaps and propose solutions to address the problem. Employing a qualitative case study design, the research utilized document analysis, semi-structured interviews, and content observation to gather data from multiple stakeholders, including legal experts, industry practitioners, and consumer organizations. The findings reveal that 55% of sustainability claims in marketing materials lack verifiable evidence, highlighting transparency as a critical concern. Weak regulatory oversight and the absence of standardized definitions for terms like "sustainable" or "eco-friendly" further complicate the issue. The study identifies transparency, monitoring, and legal accountability as key themes requiring immediate attention. The research contributes to the existing literature by integrating legal perspectives with sustainable branding strategies, particularly in the context of developing countries. It also underscores the need for regulatory reforms that emphasize clear standards and stringent sanctions. Practical implications include recommendations for regulators to enhance oversight mechanisms and for companies to prioritize transparency to gain consumer trust. Future research should explore the effectiveness of standardized sustainability metrics and evaluate cross-country regulatory frameworks. This study offers a comprehensive foundation for addressing greenwashing and fostering authentic sustainability practices.